EGFR-dependent downregulation of Capicua and the establishment of Drosophila dorsoventral polarity - Andreu, María José (Landes Bioscience, 2012)
Dorsoventral (DV) axis formation in Drosophila begins during oogenesis through the graded activation of the EGF receptor (EGFR)-Ras-MAPK signaling pathway in the follicle cell layer of the egg chamber. EGFR signaling, which is higher in dorsal follicle cells, represses expression of the sulfotransferase-encoding gene pipe, thereby delimiting a ventral domain of Pipe activity that is critical for the subsequent induction of ventral embryonic fates. We have characterized the transcriptional circuit that links EGFR signaling to pipe repression: in dorsal follicle cells, the homeodomain transcription factor Mirror (Mirr), which is induced by EGFR signaling, directly represses pipe transcription, whereas in ventral follicle cells, the HMG-box protein Capicua (Cic) supports pipe expression by repressing mirr. Although Cic is under negative post-transcriptional regulation by Ras-MAPK signaling in different contexts, the relevance of this mechanism for the interpretation of the EGFR signal during DV pattern formation remains unclear. Here, we consider a model where EGFR-mediated downregulation of Cic modulates the spatial distribution of Mirr protein in lateral follicle cells, thereby contributing to define the position at which the pipe expression border is formed.